2022
DOI: 10.1155/2022/5299370
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Does Not Reduce Abdominal Aortic Aneurysm Growth in a Mouse Model

Abstract: Background and Aims. The nacht domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3) inflammasome is upregulated in human abdominal aortic aneurysm (AAA), but its pathogenic role is unclear. The aims of this study were firstly to examine whether the inflammasome was upregulated in a mouse model of AAA and secondly to test whether the inflammasome inhibitor colchicine limited AAA growth. Methods. AAA was induced in eight-week-old male C57BL6/J mice with topical application of elastase to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In 2022, James et al reported that colchicine could not limit the growth of already established AAA [ 20 ]. James’ work and ours were both designed to investigate the impact of colchicine on AAA formation but focused on different stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, James et al reported that colchicine could not limit the growth of already established AAA [ 20 ]. James’ work and ours were both designed to investigate the impact of colchicine on AAA formation but focused on different stages.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, James et al reported that colchicine did not reduce AAA growth in a mice model with administration of colchicine (0.2 mg/kg/d via gavage) beginning from day 21 after the induction of AAA for a subsequently consecutive 69 days with the purpose to explore the therapeutic effects of colchicine on an established AAA mice model [ 20 ]. Given the facts that AAA is life threatening and associated with vascular walls’ inflammation, and colchicine could prevent neutrophils migration and interleukin-1β activation, we hypothesized that colchicine could protect against the development of AAA at the early stage.…”
Section: Introductionmentioning
confidence: 99%
“… 147 In contrast, a new model that combines two methods of inducing AAA using application of elastase to the adventitia of the infra-renal aorta and oral administration of a lysyl oxidase inhibitor holds more promise for testing drugs. 148 In this model, expansion of aortic diameter occurs over 3 months ( Figure 7 ). The model also illustrates typical human AAA characteristics of true aneurysm formation, intra-luminal thrombus, marked aortic wall inflammation, and a rupture rate of ∼30%.…”
Section: Other Targets For Therapies To Limit Abdominal Aortic Aneury...mentioning
confidence: 99%
“…The model also illustrates typical human AAA characteristics of true aneurysm formation, intra-luminal thrombus, marked aortic wall inflammation, and a rupture rate of ∼30%. 148 The use of this and other novel animal models along with rigorous study design similar to clinical trials may identify drugs more likely to translate to patients.…”
Section: Other Targets For Therapies To Limit Abdominal Aortic Aneury...mentioning
confidence: 99%
“…Zhao et al ( 81 ) conducted an animal study that demonstrated the protective effect of colchicine against the development of experimental abdominal aortic aneurysms. However, Phie et al ( 82 ) suggested that colchicine lacked efficacy in reducing the growth of abdominal aortic aneurysms in a mouse model. Although these findings primarily pertained to abdominal aortic aneurysms, they inspired intriguing possibilities regarding the potential applications of colchicine in managing IAs.…”
Section: Potential Drug Therapy Approaches In Intracranial Aneurysmsmentioning
confidence: 99%